Bharhut inscriptions - Lüders, Heinrich, 1869-1943 (Corpus inscriptionum indicarum ;, 1963)
Seventh century inscriptions found at a Buddhist site in Madhya Pradesh sometimes attributed to the kings of the Sungadynasty.